Effects of Mirror Visual Observation Priming on Upper Extremity Motor Recovery After Stroke: A Pilot Randomized Controlled Trial. - Zhuang, Jinyang; Lin, Jiali; Li, Qinying; Jia, Jie (Archives of Physical Medicine & Rehabilitation, 2025)
To investigate the priming effects of mirror visual observation (MVO) on upper extremity (UE) motor recover after stroke. Randomized, controlled, observer-blinded study. Rehabilitation Medicine Department in Tertiary Hospital. Twenty individuals (N=20) with first unilateral stroke within 1 week to 6 months. Participants were randomly divided into 2 groups: the experimental group (EG) receiving MVO with task-oriented training (MVO+TOT); and the control group (CG) receiving sham MVO+TOT. The intervention consisted of 30 minutes of MVO or sham MVO, a 10-minute break, and 30 minutes of TOT daily, 5 days a week, for 3 weeks. The primary outcome was the Fugl-Meyer Assessment Upper Extremity Motor Function Subscale (FMA_UE). The change of FMA_UE (ΔFMA_UE) before and after the intervention was assessed for clinical significance. The secondary outcomes included grip strength, the Action Research Arm Test (ARAT), and the Modified Barthel Index (MBI). All patients completed the trial without adverse reactions. The EG had a better treatment experience than the CG. Both groups showed improvements in FMA_UE, grip strength, ARAT, and MBI scores from baseline (P <.05 for all). Postintervention, there were no differences between the groups in grip strength, ARAT, and MBI scores (P >.05 for all). However, the EG showed a better improvement in FMA_UE scores compared with the CG (P =.044). The ΔFMA_UE of both groups surpassed the minimal clinically important difference (MCID). The average ΔFMA_UE difference between the groups was 10.80 (95% CI, 6.31-15.29), exceeding the MCID with statistical significance (P <.001). MVO demonstrates a priming effect that enhances the recovery of UE motor impairments poststroke with clinical significance.